Effects of Ayahuasca and its Alkaloids on Drug Dependence: A Systematic Literature Review of Quantitative Studies in Animals and Humans - Nunes, Amanda A. [UNESP]; Santos, Rafael G. dos; Osorio, Flavia L.; Sanches, Rafael F.; Crippa, Jose Alexandre S.; Hallak, Jaime E. C. (Routledge Journals, Taylor & Francis Ltd, 2016)
Recently, the anti-addictive potential of ayahuasca, a dimethyltryptamine(DMT)- and -carboline-rich hallucinogenic beverage traditionally used by indigenous groups of the Northwest Amazon and currently by syncretic churches worldwide, has received increased attention. To better evaluate this topic, we performed a systematic literature review using the PubMed database to find quantitative studies (using statistical analysis) that assessed the effects of ayahuasca or its components in drug-related symptoms or disorders. We found five animal studies (using harmaline, harmine, or ayahuasca) and five observational studies of regular ayahuasca consumers. All animal studies showed improvement of biochemical or behavioral parameters related to drug-induced disorders. Of the five human studies, four reported significant reductions of dependence symptoms or substance use, while one did not report significant results. The mechanisms responsible for the anti-addictive properties of ayahuasca and its alkaloids are not clarified, apparently involving both peripheral MAO-A inhibition by the -carbolines and central agonism of DMT at 5-HT2A receptors expressed in brain regions related to the regulation of mood and emotions. Although results are promising, controlled studies are needed to replicate these preliminary findings.
Keywords: Ayahuasca; dependence; dimethyltryptamine; hallucinogens; harmine